A CRISPR/Cas9-based system using dual-sgRNAs for efficient gene deletion in Mycobacterium abscessus - Li, Linai; Hu, Yuxiang; Wang, Dan; Li, Xin; Bao, Shengjuan; Deng, Taibing; Wang, Qinglan (Frontiers in Microbiology, 2025)
The increasing global prevalence of Mycobacterium abscessus infections presents a significant clinical challenge due to the pathogen’s intrinsic resistance to multiple antibiotics and poor treatment outcomes. Despite the necessity of genetic tools for studying its physiology, pathogenesis, and drug resistance, efficient methods for large-fragment deletions remain underdeveloped. Here, we report a CRISPR/Cas9-based dual-sgRNA system employing Streptococcus thermophilus CRISPR1-Cas9 (Sth1Cas9), enabling efficient large-fragment knockout in M. abscessus with deletion efficiencies exceeding 90% at certain loci and spanning up to 16.7 kb. Furthermore, we systematically optimized the modular arrangement of genetic components in Cas9/dual-sgRNA expression plasmids and refined their construction workflow, achieving a significant reduction in cassette loss rates while enabling single-step plasmid assembly. Notably, deletion efficiency was position-dependent rather than correlated with target size, suggesting an influence of chromatin structure on editing outcomes. As the first CRISPR/Cas9-based platform capable of kilobase-scale deletions in M. abscessus, this system advances functional genomics studies and facilitates targeted investigations into virulence and antibiotic resistance mechanisms.